Forensic Case Series: Case 1 and 2 - Lin, James; McVane, Ben; Soley, Berta (Torture Journal, 2021)
Welcome to the Torture Journal Forensic Case Series, a new section of the Torture Journal. Through this Series, we aim to provide a source of information and continuing education for health and legal practitioners involved in the forensic evaluation of survivors of torture. Cases in this section may describe unique or uncommon physical and psychological findings, illustrate barriers to a thorough evaluation, or present features that make effective articulation of a survivor’s claim challenging. Case discussions aim to provide further information about findings or reflections on how challenges were approached. We also aim to address common misconceptions about the clinical evaluation and the experience of torture. As one of the benchmarks for our discussions, we apply the principles and standards of the United Nation’s Istanbul Protocol. We hope that you will find these case studies to be a useful resource for your work with survivors of torture. Yours Truly, Guest Editors: Prof. Dr. Ben McVane, Senior Medical Educator, Libertas Center for Human Rights Prof. James Lin, Istanbul Protocol Programme Coordinator, IRCT